Competency to collaboration: an interactive process for cross-sectoral development - Debra K Olson, DNP MPH (Elsevier, 2014)
Background: A workforce functioning collaboratively to address global health challenges has been the cornerstone of recent efforts to confront threats to health at the interfaces of animals, human beings, and their environment. The concept of "one health" provides a unique perspective to building a stronger collaborative workforce founded on principles of population health. Methods: During the past several years, multiple national and international organisations have explored the competencies that are needed by a global health workforce. A competency discussion was held March 12-13, 2012, with representatives from the UN Food and Agriculture Organization, the World Organization for Animal Health, WHO, the US Department of Agriculture, Development Alternatives Inc, and Whitewater Consulting, and participants from academic institutions in Rwanda, Ethiopia, Tanzania, and the USA. Disciplines represented included public health, veterinary medicine, nursing, occupational psychology, nutrition, medicine, and education. The aim of the discussion was to review sets of competencies identified by different professional or multidisciplinary groups as important to solving complex health problems Findings: The major competency domains identified were communication, conflict resolution, systems analysis/thinking, values and ethics, creating an enabling environment and advocating change, teamwork, and leadership and management. These domains have been used to develop a framework for integrating one health competencies into programmes and curricula based on a common understanding of an interprofessional, multisectoral approach to operating effective health systems from the village to the clinic. Interpretation: Priorities include the production of a working set of competency domains. Sharing of these domains is more important than ownership or approval and informing work in global health about commonalities between and among development efforts forms the basis for accomplishment of the goal. Funding: Rockefeller Foundation, USAID RESPOND, US Centers for Disease Control and Prevention.